Epileptic kinetopsia localizes to superior parietal lobule and intraparietal sulcus - Perumal, Madhusoothanan Bhagavathi (Lippincott Williams & Wilkins, 2014)
Visual hallucinations are common symptoms of seizures affecting primary and association cortices, and can provide vital information about the ictal onset zone. Epileptic kinetopsia, defined as illusionary movement of stationary objects in the visual field, was reported in a patient with a tumor in the temporal-parietal-occipital (TPO) junction. Intracranial stimulation of TPO junction did not evoke kinetopsia and the site of onset of this phenomenon is unknown.(1) We describe a patient with ictal kinetopsia whose seizure onset zone was localized with intracranial EEG.